2000
DOI: 10.1074/jbc.m003826200
|View full text |Cite
|
Sign up to set email alerts
|

Defective Uptake and Utilization of Long Chain Fatty Acids in Muscle and Adipose Tissues of CD36 Knockout Mice

Abstract: The transmembrane protein CD36 has been identified in isolated cell studies as a putative transporter of long chain fatty acids. In humans, an association between CD36 deficiency and defective myocardial uptake of the fatty acid analog 15-(p-iodophenyl)-3-(R,S)-methyl pentadecanoic acid (BMIPP) has been reported. To determine whether this association represents a causal link and to assess the physiological role of CD36, we compared tissue uptake and metabolism of two iodinated fatty acid analogs BMIPP and 15-(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
486
3
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 630 publications
(524 citation statements)
references
References 45 publications
34
486
3
1
Order By: Relevance
“…In the absence of CD36, the heart, which normally derives most of its energy from fatty acids, instead relies more heavily on glucose. This confirmed our studies with the radio labeled tracers 125 I-BMIPP (a non-metabolizable fatty acid analog), 125 I-IPPA (a metabolizable fatty acid analog) and 8-fluorodeoxyglucose (a glucose analog), which were initiated because of the observation that CD36 KO mice have fasting hypoglycemia (Coburn, Knapp, Febbraio, Beets, Silverstein, & Abumrad, 2000). Under normal and high fat conditions, we found that the CD36 KO mouse heart is entirely compensated in terms of ATP and acylCoA fatty acids by utilization of glucose (Kuang, Febbraio, Wagg, Lopaschuk, & Dyck, 2004).…”
Section: Other Functions Of Cd36 That May Impact Cardiovascular Diseasesupporting
confidence: 82%
See 1 more Smart Citation
“…In the absence of CD36, the heart, which normally derives most of its energy from fatty acids, instead relies more heavily on glucose. This confirmed our studies with the radio labeled tracers 125 I-BMIPP (a non-metabolizable fatty acid analog), 125 I-IPPA (a metabolizable fatty acid analog) and 8-fluorodeoxyglucose (a glucose analog), which were initiated because of the observation that CD36 KO mice have fasting hypoglycemia (Coburn, Knapp, Febbraio, Beets, Silverstein, & Abumrad, 2000). Under normal and high fat conditions, we found that the CD36 KO mouse heart is entirely compensated in terms of ATP and acylCoA fatty acids by utilization of glucose (Kuang, Febbraio, Wagg, Lopaschuk, & Dyck, 2004).…”
Section: Other Functions Of Cd36 That May Impact Cardiovascular Diseasesupporting
confidence: 82%
“…CD36 KO mice have a fasting hypoglycemia and different energy substrate use in heart (Kuang, Febbraio, Wagg, Lopaschuk, & Dyck, 2004). Uptake of fatty acid analogs was specifically reduced in muscle and adipocytes of mice, and has been shown to be reduced in heart of CD36-deficient humans (Coburn, Knapp, Febbraio, Beets, Silverstein, & Abumrad, 2000,Watanabe, et al, 1998,Hwang, et al, 1998,Tanaka, et al 2001). …”
Section: Cd36 Structure and Expressionmentioning
confidence: 98%
“…Transgenic mice overexpressing CD36 had reduced blood lipid levels (Aitman et al, 1999). CD36-null mice showed reduced fatty acids uptake in various tissues (Coburn et al, 2000). DPP4 is identical to T-cell activation antigen CD26 (Koch and Shows, 1980) and to adenosine deaminase complexing protein 2 (Morrison et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent evidence demonstrates that the membrane protein CD36 (fatty acid translocase), which is a facilitator of long-chain fatty acids (Coburn et al, 2000), is deficient in a rat model of human metabolic syndrome X (Aitman et al, 1999).…”
Section: Discussionmentioning
confidence: 99%